Simulation-based capital models: testing, justifying and communicating choices. A report from the life aggregation and simulation techniques working party. (17th April 2017) - Androschuck, T.; Gibbs, S.; Katrakis, N.; Lau, J.; Oram, S.; Raddall, P.; Semchyshyn, L.; Stevenson, D.; Waters, J.
Abstract: The development of an economic capital model requires a decision to be made regarding how to aggregate capital requirements for the individual risk factors while taking into account the effects of diversification. Under the Individual Capital Adequacy Standards framework, UK life insurers have commonly adopted a correlation matrix approach due to its simplicity and ease in communication to the stakeholders involved, adjusting the result, where appropriate, to allow for non-linear interactions. The regulatory requirements of Solvency II have been one of the principal drivers leading to an increased use of more sophisticated aggregation techniques in economic capital models. This paper focusses on a simulation-based approach to the aggregation of capital requirements using copulas and proxy models. It describes the practical challenges in parameterising a copula including how allowance may be made for tail dependence. It also covers the challenges associated with fitting and validating a proxy model. In particular, the paper outlines how insurers could test, communicate and justify the choices made through the use of some examples.